2018
DOI: 10.1136/archdischild-2017-314451
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapies in neonatology: a new hope

Abstract: Despite progress made in neonatal intensive care, complications of extreme preterm birth still contribute as the main cause of death to children below 5 years of age. Stem cell-based therapies-mesenchymal stromal cells in particular-offer a new hope in preventing and/or restoring organ damage in extreme preterm infants. Early phase clinical trials, fueled by promising preclinical studies on lung and brain injury, have begun. While the enthusiasm in the neonatal community is palpable, much more needs to be lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…A recent Canadian workshop group of neonatologists acknowledged cell-based therapies as promising for BPD (22), and highlighted that successful translation requires careful consideration of antenatal, perinatal, and postnatal factors. They and others also emphasize the need for evidence-based approaches in designing and executing these studies (23, 24). Our study provides epidemiologic evidence that HPSCs and MSCs present at birth vary in concentration among preterm infants who later develop BPD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Canadian workshop group of neonatologists acknowledged cell-based therapies as promising for BPD (22), and highlighted that successful translation requires careful consideration of antenatal, perinatal, and postnatal factors. They and others also emphasize the need for evidence-based approaches in designing and executing these studies (23, 24). Our study provides epidemiologic evidence that HPSCs and MSCs present at birth vary in concentration among preterm infants who later develop BPD.…”
Section: Discussionmentioning
confidence: 99%
“…This process is mimicking the behavior of circulating progenitor cells during cancer development (109). Nowadays cell-based therapies are becoming more relevant (119,120) and considering the homing properties of endothelial precursor cells (109,121), it could be possible to engineer such early EPCs that would carry therapeutic genes and targeting angiogenesis (109,122,123). Collet et al confirmed this hypothesis (118).…”
Section: Vascular Normalization Strategies Vs Anti-angiogenic Therapiesmentioning
confidence: 94%
“…Descubiertas en 1976, las MSC se describieron por primera vez en la médula ósea como células similares a fibroblastos cruciales para la regulación de las células madre hematopoyéticas. (Thébaud, 2018) Las células madre tienen la capacidad de dar origen a cualquier otra célula del cuerpo y reemplazar a las que se van muriendo, o liberar al entorno moléculas que contribuyen en la reparación de daños provocados por enfermedades, traumas y el mismo fenómeno de envejecimiento. Estas células madre poseen al menos dos características principales: tienen la capacidad de diferenciarse en cualquier tipo de célula especializada, si reciben el estímulo adecuado (diferenciación), al tiempo que pueden conservarse como tales y producir indefinidamente células madre (autorenovación).…”
Section: Introductionunclassified